The Use Nanoparticles Tomatoes Flour As Source of Fiber on Chicken Nuggets - Herly Evanuarini; Agus Susilo; Uun Yanuhar; Adelya Desi Kurniawati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2022)
The purpose of this research was to determine the use nanoparticle tomatoes flour as source fiber to increased the quality of chicken nuggets. The materials used in research are nuggets made from chicken meat with optional ingredient other flour tapioca, pepper, onion white, salt, sugar and bread flour.  The addition of nanoparticles of tomato flour on chicken nuggets by treatment carried out. Experimental method laboratory used as a method test laboratory. The Completely Randomized Design was used as an experimental design with 4 treatments and 5 replications. The treatment use control that is without the addition of nanoparticles tomato flour (P0), P1 (addition of nanoparticles tomato flour 1%), P2 (2%), and P3 (3%) of the total chicken meat used. The variables measured are protein content, fiber content, pH value, and sensory quality (color, taste, aroma, texture, and acceptance). The addition of nanoparticles tomatoes flour (Lycopersicum esculentum Mill) on chicken nuggets gives highly significant effect (P<0.01) on protein content, fiber, pH value, and sensory quality of color, taste, aroma, texture, and acceptance. Protein content in chicken nuggets with addition nanoparticles tomatoes flour (Lycopersicum esculentum Mill) produced range between 13.1 – 16.17. The average rate of chicken nuggets fiber range between 0.79 – 1.04%. Chicken nuggets pH value between 5.86 – 6.16. Panelists score on quality organoleptic color chicken nuggets addition nanoparticles tomatoes flour range between 3.15 – 4.50, score taste ranges between 3.25 – 4.65, score aroma ranges from 3.20-4.55 texture range 3.15 – 4.60 dan acceptance 3.40 – 4.70. The research conclusion is the addition of tomatoes flour in the form of nanoparticles could improved the quality of nuggets and additions by 3 percent make chicken nuggets with best quality.